2006
DOI: 10.1128/aac.00438-06
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Imipenem-Hydrolyzing Enzyme KPC-2 among Multiple Carbapenem-Resistant Escherichia coli Clones in Israel

Abstract: Carbapenem resistance in Escherichia coli is rare. We report four genetically unrelated carbapenem-resistant E. coli isolates cultured from four patients hospitalized in Tel Aviv Medical Center. PCR, sequencing, and Southern blot analysis identified KPC-2 as the imipenem-hydrolyzing enzyme in all four strains, carried on different plasmids with a possible common origin. This is the first discovery of KPC-2 in E. coli and the first report of this enzyme originating outside the United States.Carbapenem resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 21 publications
4
107
1
3
Order By: Relevance
“…Little is known about the role gene expression plays in KPC-mediated resistance or how the level of expression may affect susceptibility testing. Hydrolysis of carbapenems by KPCs has been demonstrated in vitro (1,21,22); however, multiple studies have reported variability in susceptibility testing of KPC-producing clinical isolates (2,3,13,22). Although variation in KPC enzyme production could contribute to the variability seen during susceptibility testing, it is difficult to assess the influence of the KPC ␤-lactamase on susceptibility testing using clinical isolates which may harbor multiple ␤-lactamases and may have alterations in outer membrane proteins (4,7,9,10,21,24).…”
mentioning
confidence: 99%
“…Little is known about the role gene expression plays in KPC-mediated resistance or how the level of expression may affect susceptibility testing. Hydrolysis of carbapenems by KPCs has been demonstrated in vitro (1,21,22); however, multiple studies have reported variability in susceptibility testing of KPC-producing clinical isolates (2,3,13,22). Although variation in KPC enzyme production could contribute to the variability seen during susceptibility testing, it is difficult to assess the influence of the KPC ␤-lactamase on susceptibility testing using clinical isolates which may harbor multiple ␤-lactamases and may have alterations in outer membrane proteins (4,7,9,10,21,24).…”
mentioning
confidence: 99%
“…13 Furthermore, transfer of carbapenemase-containing plasmids into E. coli K-12 is associated with a substantially lower MIC in the recipient. 14 These observations suggest that attributes of the host strain contribute substantially to the phenotypic expression of carbapenem resistance. We therefore hypothesized that CRE strains could be modulated using small molecules to lower the carbapenem MIC into the susceptible range and thereby restore carbapenem therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 89%
“…Outro aspecto importante reportado no trabalho foi que vários isolados se apresentaram sensíveis ao imipenem (5) . (11) .…”
Section: Materials E Métodounclassified